La España de la estabilización y el desarrollo en perspectiva francesa (1958-1969) - Esther M. Sánchez Sánchez (Mélanges de la Casa de Velázquez, 2004)
The purpose of this article is to analyse the reaction of the French government and French employers to the economic policy applied in Spain from the late 1950s, especially following approval of the 1959 Stabilisation Plan and Spain’s accession to some of the principal international economic organisations, such as the OECD, the IMF and the World Bank. It particularly examines the way in which the French government of General de Gaulle (1958-1969) reacted to Spain’s Stabilisation and Development plans, the lines of action proposed by French economic policy makers to take advantage of the new context of Spanish liberalisation and growth, and the obstacles that government and employers came up against in attempting to expand and consolidate their positions beyond the Pyrenees.